Culture and Competencies: A Multi-Country Examination of Reference Service Competencies - Saunders, Laura; Kurbanoglu, Serap; Wilkins Jordan, Mary; Boustany, Joumana; Chawner. Branda Filas, Matylda; Haddrow, Gaby; van Helvoort, Jos Kakouri, Mersini; Landøy, Ane; Minch, Karolina; Oliver, Gillian; Polydoratou, Panayiota; Repanovici, Angela; et al. (2013)
Reference librarians have the opportunity to interact with patrons and colleagues of many different backgrounds, languages, and cultures as a result of our increasingly interconnected and peripatetic world. In order to provide the best possible service to these varied communities, reference librarians should understand some of the culture differences that exist across countries, and in particular, the differences in the way that reference services are conceived and delivered in different countries. This study explores some of these differences in reference services by surveying current practitioners in thirteen countries to find out which competencies they believe are most important for academic reference librarians right now, and in the near future. The results of this study highlight some important commonalities and differences, and could help reference librarians to manage and meet the expectations of their international patrons, and perhaps help them to prepare for an international job experience of their own. Academic reference librarians may be interested to see the extent to which their counterparts in other countries face similar challenges and expectations with regard to delivering reference services. Teaching faculty in library science programs will be interested to understand reference competencies and expectations in other countries, especially as they teach greater numbers of international students or consider collaborating with international colleagues. In addition, an international understanding is important in developing students who can compete in a global job market.
Projekt MZOS
ENG